2023
DOI: 10.1177/13684302231156399
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive social norms and nationals’ positive intergroup orientations toward refugees: The moderating role of initial prejudice and intergroup contact

Abstract: Research on the interplay between inclusive norms and intergroup contact on improving intergroup orientations has yielded conflicting results, suggesting either that an experience of personal contact is necessary to have a positive effect of inclusive norms or that such personal experience is not always necessary. To clarify this issue, across four studies ( N = 835), we investigated the influence of inclusive norms on positive intergroup orientations as a function of personal experiences of intergroup contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Social norms that refer to ingroup members' (dis)approval of behavior toward outgroups, and generally nature of the intergroup relationship, stemming from the ingroup are called ingroup injunctive norms (Cialdini et al, 1990). Considerable research in peaceful settings showed that ingroup injunctive norms shape approachrelated intergroup attitudes and behavior (e.g., Jugert et al, 2011;Terry & Hogg, 2001;Tropp et al, 2014;Valsecchi et al, 2023). For instance, two studies in Belgium and Switzerland found that perceived injunctive norms regarding helping behaviors toward migrants promoted and maintained helping actions for migrants within social networks (Roblain et al, 2020).…”
Section: Ingroup Injunctive Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social norms that refer to ingroup members' (dis)approval of behavior toward outgroups, and generally nature of the intergroup relationship, stemming from the ingroup are called ingroup injunctive norms (Cialdini et al, 1990). Considerable research in peaceful settings showed that ingroup injunctive norms shape approachrelated intergroup attitudes and behavior (e.g., Jugert et al, 2011;Terry & Hogg, 2001;Tropp et al, 2014;Valsecchi et al, 2023). For instance, two studies in Belgium and Switzerland found that perceived injunctive norms regarding helping behaviors toward migrants promoted and maintained helping actions for migrants within social networks (Roblain et al, 2020).…”
Section: Ingroup Injunctive Normsmentioning
confidence: 99%
“…Perceived positive peer group norms about cross-ethnic friendships (i.e., ingroup injunctive norms) were linked to interethnic friendship formation (Jugert et al, 2011;Tropp et al, 2014). Likewise, inclusive norms were linked to greater willingness to engage in future contact with immigrants in France (Valsecchi et al, 2023).…”
Section: Ingroup Injunctive Normsmentioning
confidence: 99%
“…There are two types of moderators (West & Brückmüller, 2013): those that describe pre‐existing elements unrelated to IIC tasks and those that signal IIC task characteristics. Regarding the former set of moderators, IIC was more effective for participants high on national and ethnic identification (Bagci, Piyale, & Ebcim, 2018; Stathi & Crisp, 2008), intergroup anxiety (Birtel & Crisp, 2012), conservatism, outgroup dehumanization (Borinca, Çelik, et al, 2022), and initial prejudices (Valsecchi et al, 2024; West et al, 2017), but low on previous intergroup contact (Hoffarth & Hodson, 2016). Besides, imagined interactions with ethnic groups toward whom prejudices are deeply embedded in the culture were not effective in decreasing biases (Asbrock et al, 2013), as negative intergroup expectations typically lead to negative interactions (Borinca et al, 2021; MacInnis & Page‐Gould, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rather intuitive nature of the relationship between ingroup norms and prejudice, some researchers have pointed to important boundary conditions and moderators of this relationship, such as intergroup threat (Falomir‐Pichastor, Muñoz‐Rojas, Invernizzi, & Mugny, 2004), existing prejudice (Valsecchi, Berent, Borinca, Green, & Falomir‐Pichastor, 2024), held values (Oyamot Jr., Fisher, Deason, & Borgida, 2012), and different forms of intergroup contact (Valsecchi et al, 2024; Visintin et al, 2020; White et al, 2021). A particularly relevant individual difference to consider is political ideology, defined as a set of “socially shared but competing philosophies of life and how it should be lived (and how society should be governed)” (Jost, Federico, & Napier, 2009, p. 309).…”
Section: Introductionmentioning
confidence: 99%
“…contact (Valsecchi et al, 2024;Visintin et al, 2020;White et al, 2021). A particularly relevant individual difference to consider is political ideology, defined as a set of "socially shared but competing philosophies of life and how it should be lived (and how society should be governed)" (Jost, Federico, & Napier, 2009, p. 309).…”
mentioning
confidence: 99%